Is Low Birth Weight a Risk Factor for Early Childhood Caries? : A Nationwide Retrospective Cohort (Indian Journal of Public Health Research & Development, 2020)
Objectives: We investigated the impact of birth weight on early childhood caries (ECC) to identify theassociation between birth-related factors and oral health using Korea’ national health screening database.Methods: Children born between 2008 and 2012 who had undergone the first and second health screening atleast once and had been confirmed ECC through ECC examination in the first to third oral health screeningwere included. They were classified according to the presence of dental caries (ECC or non-ECC group)and their birth weight (low [LBW;
Keywords: Early childhood caries, Low birth weight, Oral health